Quality Assurance in Qualifications Frameworks : issues paper. Dublin Castle 12-13 march 2013 - Murray, Jim [Verfasser] (My University, 2013)
"This issues paper supported the conference "Quality Assurance in Qualifications Frameworks" hosted by Quality and Qualifications Ireland (QQI) on the 12 and 13 March in Dublin Castle, as part of the Irish Presidency of the Council of the European Union. It includes these four themes: Integrating Quality Assurance and Qualifications Frameworks to improve education and training systems / Using Quality Assurance and Qualifications Frameworks to improve the labour market relevance of qualifications / Quality Assurance and Qualifications Frameworks in facilitating the Validation of Non-formal and Informal learning / Promoting confidence in Europe's qualifications on a global scale." (BIBB-Doku)
Dearbhú Cáilíochta i gCreataí Cáilíochtaí
Keywords: S 1 Stufen der Berufsbildung; L 6.2 Qualitätsmanagement/Qualitätssicherung; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; Qualitätssicherung; Bildungssystem; Europäischer Qualifikationsrahmen; Nationaler Qualifikationsrahmen; EU-Bildungspolitik; Europa